Microstructure and tensile properties of as-extruded Mg-Sn-Y alloys - 赵宏达 秦高梧 任玉平 裴文利 陈冬 郭运 (Transactions of Nonferrous Metals Society of China, 2010)
The microstructure and tensile properties of the Mg-1.0%Sn-xY（x=1.5%,3.0%,3.5%,atom fraction）alloys extruded indirectly at 350℃ were investigated by means of optical microscopy,scanning electron microscopy and tensile test.The mean grain sizes ofα-Mg matrix in the three extruded alloys are 6,8 and 12μm,respectively,slightly increasing with the addition of Y. The relationship between microstructure and strength was discussed in detail.The results show that the addition of Y has little effect on the grain refinement of the as-extruded Mg-Sn based alloys above.The only MgSnY phase is detected in the Mg-Sn-1.5%Y alloy, and the Sn3Y5 phase in the Mg-Sn-3.5%Y alloy,whereas both of them simultaneously exist in the Mg-Sn-3.0%Y alloy.The particle shape of MgSnY and Sn3Y5 phase,inherited from the solidification,has little change before and after hot extrusion.Mg-Sn-3.0%Y alloy has the highest ultimate tensile strength（UTS）,305 MPa,by over 50%compared with that of the other two alloys.